Cochlear implant and tinnitus-a meta-analysis - Borges,Alda Linhares de Freitas (2021)
Abstract Introduction Tinnitus is a frequent symptom in cochlear implant patients, often reported as persistent and disabling in implant candidates. Tinnitus is rarely considered in the preoperative evaluation of patients who are eligible for cochlear implantation. Many studies have shown that a cochlear implant leads to a significant change in the perception of tinnitus. Objective To identify evidence in the scientific literature indicating that cochlear implant in eligible patients with tinnitus can improve tinnitus perception. Methods One hundred forty articles were found from nine databases, and 20 articles from the gray literature mentioned the relationship between cochlear implant and tinnitus perception in patients eligible for cochlear implant. The PICOS (population, intervention, comparison, and outcome) strategy, was used to define the eligibility criteria. The studies that met the inclusion criteria for this second step were included in a qualitative synthesis, and each type of study was analyzed using the Joanna Briggs Institute critical appraisal checklist for quasi-experimental studies and the Joanna Briggs Institute critical appraisal checklist for randomized clinical trials. Results The full texts of 11 articles were read, and 6 studies were selected for the meta-analysis. The total sample size in the evaluated articles was 136 patients with tinnitus who were eligible for cochlear implantation. Conclusions Taken together, these findings support the feasibility of cochlear implantation to reduce the perception of tinnitus, thus providing a new perspective in the treatment of tinnitus in patients with hearing loss who are candidates for cochlear implantation.